KELAYAKAN LKPD BERBASIS PROBLEM BASED LEARNING PEMBELAJARAN IPAS KELAS IV SDN 36 PONTIANAK KOTA - Mayuni, Irin; Kartono, Kartono; Wiyono, Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to produce a product in the form of a Student Worksheet (LKPD) based on Problem-Based Learning (PBL) for fourth-grade Natural and Social Sciences (IPAS) at SDN 36 Pontianak Kota, which is feasible in terms of both content and design, as well as to describe students"™ responses to the developed product. The research and development method used is the 4D development model (Define, Design, Develop). This study employed product validation questionnaires by experts. The average score obtained in the content aspect was 96.25% with the criterion of "Highly Feasible," while the design aspect obtained an average score of 83% with the criterion of "Highly Feasible" for the PBL-based Student Worksheet developed. These results were also supported by students"™ responses to the developed worksheet. This was evident from the questionnaire results, which obtained an average percentage of 84.79% with the criterion of "Very Positive." Therefore, it can be concluded that the developed PBL-based Student Worksheet is feasible for use in the learning process.